2019
DOI: 10.1038/s41467-019-09414-4
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid longitudinal-transverse phonon polaritons

Abstract: Phonon polaritons, hybrid light-matter quasiparticles resulting from strong coupling of the electromagnetic field with the lattice vibrations of polar crystals are a promising platform for mid-infrared photonics but for the moment there has been no proposal allowing for their electrical pumping. Electrical currents in fact mainly generate longitudinal optical phonons, while only transverse ones participate in the creation of phonon polaritons. We demonstrate how to exploit long-cell polytypes of silicon carbid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 46 publications
3
52
0
Order By: Relevance
“…Here the Fröhlich resonance, radiative in the far field, plays the part of the bright state while longitudinal modes are dark. This behavior is analogous to the weak phonon coupling previously observed in larger 4H-SiC particles, where the weak phonon frequency was determined by the lattice periodicity rather than particle morphology [9,27]. Fano interference acts to reduce the bright state's far-field scattering, while increasing absorption as energy is funneled into nonradiative dark states [43,44].…”
Section: Scattering From Sic Nanospheressupporting
confidence: 74%
See 2 more Smart Citations
“…Here the Fröhlich resonance, radiative in the far field, plays the part of the bright state while longitudinal modes are dark. This behavior is analogous to the weak phonon coupling previously observed in larger 4H-SiC particles, where the weak phonon frequency was determined by the lattice periodicity rather than particle morphology [9,27]. Fano interference acts to reduce the bright state's far-field scattering, while increasing absorption as energy is funneled into nonradiative dark states [43,44].…”
Section: Scattering From Sic Nanospheressupporting
confidence: 74%
“…We demonstrated that the negative dispersion of optical phonons, and the existence of a finite transverse frequency bounding the reststrahlen band from below, leads to a rich and unique nonlocal phenomenology. In particular, opening the possibility to resonantly couple photonic excitations to propagative longitudinal modes makes it possible to engineer hybrid longitudinal-transverse SPhPs, recently highlighted as an important stepping stone toward the realization of electrically pumped SPhP devices [27], in generic nanoscale objects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This band is characterized by a negative real part of the permittivity. A characteristic feature of SPhPs 1 , 8 , 9 is their ability to confine radiation to subdiffractional length scales 10 , 11 , benefitting various applications such as surface-enhanced infrared spectroscopy 4 , 12 , 13 , thermal energy harvesting 14 , and nanoscale heat transfer 3 , among others. In contrast to diffraction-limited electromagnetic modes in dielectric waveguides, the polariton wavelength can be continuously reduced by shrinking the dimensions of polariton-supporting materials.…”
Section: Introductionmentioning
confidence: 99%
“…Hybrid modes produced by plasmons in graphene and molecular vibrations of absorbates on the graphene surface may enable high-selectivity sensing mechanisms [216,217]. A special case of hybrid modes is hybrid longitudinal-transverse phonon polaritons [218]. Polaritonic heterostructures with phase change materials enable persistent switching of polaritonic response under thermal and optical stimuli [219].…”
Section: Dn Basov Et Al: Polariton Panoramamentioning
confidence: 99%